APPROPRIATE DATA PREPARATION FOR POLYMER FLOOD PROCESS - Herlan Adim (Scientific Contributions Oil and Gas, 2003)
Oil production from reservoirs by natural (primary) drive mechanisms is often an inefficient process which may leave considerably more â€œresidualâ€ oil trapping behind the reservoir than can improve mobility and sweep efficiency where permeability variation occurs. Polymer flood recovery.